Humor comic strips in the education for sexual diversity - Margonari, Denise Maria [UNESP]; Braga Jr, Amaro Xavier (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2015)
The work analyzes the role of humor in Brazilian comic strips, whose theme is related to sexual diversity, with the aim of presenting possibilities for theme analysis, such as cross-content, in education for sexual diversity. It consists of a survey of Brazilian publications, with a description of their practices. Discusses the concept of humor historically and its links with moral deformity of ideas and ethical condemnation of laughter. Proposing a redefinition of perspective of this conception of laughter on the subject of diversity, as object of resistence of authors defending their ideals, we encourage the use of comics as a teaching tool in the classroom.
Keywords: Comics; Humor; Sexual education